AWARENESS OF DRUG USE OF OUTPATIENTS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2021)
Objective: To survey outpatient awareness of drug use at Thong Nhat Hospital.Subjects and methods: cross-sectional descriptive study on 120 patients who were given health insurance drugs waiting to take drugs, before entering the counseling room from September 1st, 2020 to December 1st, 2020 at the Thong Nhat hospital.Results: Patients based on reference of the drug name in the prescription at 51.15% and take drugs each time according to the prescription when being prescribed many drugs at the same time (57.50%). Using refresh water to take medicine accounted for 68.33%. There were 59.16% of patients taking the whole pill. Some patients took medicine following the other way such as breaking the pill before taking it (11.67%); Dissolve the drug in water (7.5%). Most of the patients (89.17%) learned about drug instructions. Doctors were the source of information for patients (61.67%) and the majority ofpatients (57.5%) heard counseling on drug use.Conclusion: The proportion of patients based on reference of the drug name in the prescription and taking each time according to the prescription when being prescribed many drugs at the sametime was moderate. Most patients used refresh water to take medicine and take whole pill. Most patients learned about medication instructions. Physicians were the primary source of informationfor patients and the majority of patients heard advice about drug use.
Keywords: Drug use awareness, outpatients